Answer:
[tex](r,s) => (2,-1);(2,0); (1,-1); (4,-1);(2,3)[/tex]
Step-by-step explanation:
Given
[tex](r - 2)(s +1) = 0[/tex]
Required
Write at least 5 pair of numbers
[tex](r - 2)(s +1) = 0[/tex]
This can be split to be
[tex]r -2 = 0[/tex] --- (1)
or
[tex]s + 1 = 0[/tex] --- (2)
Solve for r in (1)
[tex]r = 2[/tex]
This means that for whatever value that s assumes, the equation will always be true when r = 2
Solve for s in (2)
[tex]s = -1[/tex]
This means that for whatever value that r assumes, the equation will always be true when s = -1
So, we can make use of the following pair
[tex](r,s) => (2,-1);(2,0); (1,-1); (4,-1);(2,3)[/tex]